Kompetensi Ahli Kepabeanan pada Perusahaan Kargo International - Primadi Candra Susanto; Yosi Pahala; Euis Saribanon (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2020)
The purpose of this study is to find out more about the competence of human resources custom expert based on performance appraisals and assessments in order to help organizations to have competent and reliable human resources in the work place. Through various routine development, training and evaluation activities, human resource competencies will be more optimal and lead to improving organizational performance of human resource custom expert, the main problem is the lack of standardization of customs expert competence. This quantitative research uses multiple correlation regression with the sample using a sampling technique that provides equal opportunities for each element (member) of the population to be seleted as sample member.The research sample consisted of 37 respondents from 19 companies that werw considered as representative of the customs service business sector in the tanjung priok port area of Jakarta. The method used action research is research that aims to develop the most efficient work methods. The result showed that there was a positive and significant direct effect, among others, performance appraisal had a positive and significant effect on the competence of human resources customs expert, a positive and significant effect on the competence of human resource custom experts, performance appraisal and joint assessment had a positive effect and significants to the competence of human resources custom expert.Keywords: HR competence of custom experts; performance appraisals; assessment